Antibiotic Resistance Patterns of Pseudomonas spp. Isolated from the River Danube - Kittinger, Clemens; Lipp, Michaela; Baumert, Rita; Folli, Bettina; Koraimann, Günther; Toplitsch, Daniela; Liebmann, Astrid; Grisold, Andrea J.; Farnleitner, Andreas H.; Kirschner, Alexander; Zarfel, Gernot (Frontiers in Microbiology, 2016)
Spread and persistence of antibiotic resistance pose a severe threat to human health, yet there is still lack of knowledge about reservoirs of antibiotic resistant bacteria in the environment. We took the opportunity of the Joint Danube Survey 3 (JDS3), the world's biggest river research expedition of its kind in 2013, to analyse samples originating from different sampling points along the whole length of the river. Due to its high clinical relevance, we concentrated on the characterization of Pseudomonas spp. and evaluated the resistance profiles of Pseudomonas spp. which were isolated from eight sampling points. In total, 520 Pseudomonas isolates were found, 344 (66.0%) isolates were identified as Pseudomonas putida, and 141 (27.1%) as Pseudomonas fluorescens, all other Pseudomonas species were represented by less than five isolates, among those two P. aeruginosa isolates. Thirty seven percent (37%) of all isolated Pseudomonas species showed resistance to at least one out of 10 tested antibiotics. The most common resistance was against meropenem (30.4%/158 isolates) piperacillin/tazobactam (10.6%/55 isolates) and ceftazidime (4.2%/22 isolates). 16 isolates (3.1%/16 isolates) were multi-resistant. For each tested antibiotic at least one resistant isolate could be detected. Sampling points from the upper stretch of the River Danube showed more resistant isolates than downriver. Our results suggest that antibiotic resistance can be acquired by and persists even in Pseudomonas species that are normally not in direct contact with humans. A possible scenario is that these bacteria provide a reservoir of antibiotic resistance genes that can spread to related human pathogens by horizontal gene transfer.